Purification and characterization of an extracellular beta-xylosidase from Pseudozyma hubeiensis NCIM 3574 (PhXyl), an unexplored yeast - Mhetras, Nutan; Liddell, Susan; Gokhale, Digambar (AMB Express, 2016)
This paper reports on the production of beta-xylosidase from an unexplored yeast, Pseudozyma hubeinsis. The expression of this enzyme could be induced by beech wood xylan when the yeast was grown at 27 degrees C. The enzyme was purified to homogeneity as a glycoprotein with 23 % glycosylation. The purification protocol involved ammonium sulphate precipitation, QAE-Sephadex A50 ion exchange chromatography and sephacryl-200 column chromatography which resulted in 8.3-fold purification with 53.12 % final recovery. The purified enzyme showed prominent single band on SDS-PAGE. It is a monomeric protein of 110 kDa molecular weight confirmed by SDS-PAGE followed by MALDI-TOF mass spectrometry (112.3 kDa). The enzyme was optimally active at 60 degrees C and pH 4.5 and stable at pH range (4-9) and at 50 degrees C for 4 h. Chemical modification studies revealed that active site of the purified enzyme comprised of carboxyl, tyrosine and tryptophan residues. The carboxyl residue is involved in catalysis and tryptophan residue is solely involved in substrate binding. The best match from the search of the NCBInr database was with gi vertical bar 808364558 glycoside hydrolase of Pseudozyma hubeiensis SY62 with 26 % sequence coverage confirming that it is a glycoside hydrolase/beta-glucosidase. From the search of customized SWISSPROT database, it was revealed that SWISSPROT does not contain any entries that are similar to the purified enzyme.